2012
DOI: 10.5423/rpd.2012.18.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Efficacy of Endophytic Bacteria Flavobacterium hercynim EPB-C313 for Control of Chinese Cabbage Clubroot

Abstract: Clubroot of Chinese cabbage by Plasmodiophora brassicae, was found to be high virulent to the Chinese cabbage, turnips and cabbage. It this study, the endophytic bacteria Flavobacterium hercynium EPB-C313, which was isolated from tissues of Chinese cabbage, was investigated the antimicrobial activity on the inactivation of resting spores and its control effect on clubroot disease by bioassay. The bacterial cells, culture solutions, and culture filtrates of F. hercynium EPB-C313 inactivate the resting spores of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Some species of the genera Flavisolibacter, Massilia and Pseudomonas have been related to the suppression of tipping disease caused by Rhizoctonia solani in organic lettuce crops (Bonanomi et al., 2018). The endophytic bacterium Flavobacterium hercynium , isolated from chinese cabbage, showed antimicrobial activity inactivating the spores of P. brassicae and confirmed the efficacy in the biological control of clubroot (Hahm et al., 2012). Bacillus subtilis is cited as an antagonist to P. brassicae (Einhorn, Bochow, Huber, & Krebs, 1991) and B. cereus , B. megaterium , e. B. toyonensis, isolated from tomato plants in these same areas, are cited as antagonists to Fusarium oxysporum f sp.…”
Section: Discussionmentioning
confidence: 82%
“…Some species of the genera Flavisolibacter, Massilia and Pseudomonas have been related to the suppression of tipping disease caused by Rhizoctonia solani in organic lettuce crops (Bonanomi et al., 2018). The endophytic bacterium Flavobacterium hercynium , isolated from chinese cabbage, showed antimicrobial activity inactivating the spores of P. brassicae and confirmed the efficacy in the biological control of clubroot (Hahm et al., 2012). Bacillus subtilis is cited as an antagonist to P. brassicae (Einhorn, Bochow, Huber, & Krebs, 1991) and B. cereus , B. megaterium , e. B. toyonensis, isolated from tomato plants in these same areas, are cited as antagonists to Fusarium oxysporum f sp.…”
Section: Discussionmentioning
confidence: 82%
“…brassicae [ 44 , 46 , 47 ]; Streptomyces spp. [ 48 , 49 ] and Streptomyces griseoruber A316 [ 50 ] from the family Streptomycetaceae have been reported to reduce the severity of clubroot disease; Flavobacteriumhercynim EPB-C313, an endophytic bacteria of the family Flavobacteriaceae, has been used to control Chinese cabbage clubroot [ 51 ]. In this study, we identified 1, 1, and 7 OTUs in the asymptomatic samples belonging to Bacillaceae, Streptomycetaceae, and Flavobacterium families, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the largest bacterial group at the genus level was Flavobacterium, whose abundance in the treatment group was about 2% higher than that in the control group, but there was no significant difference between these two groups. Flavobacterium hercynium EPB-C313 has been found to have a significant inhibitory effect on P. brassicae (Hahm et al, 2012). A previous study has shown that Bacillus subtilis XF-1 can promote the growth of Flavobacterium and that Flavobacterium has a potential role in the prevention and treatment of clubroot disease (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%